Follow the signs archetypes of consciousness embodied in the signs of language - Sangster, Rodney B., 1942- (Studies in functional and structural linguistics ;, 2020)
"In this his latest book, Sangster presents a comprehensive theory that takes the cognitive view of language in a promising new direction, based upon how linguistic signs relate to one another at different levels of consciousness. At the rational level, where signs are necessarily experienced in context, they are primarily polysemic. At the transpersonal or pre-contextual level, however, they are monosemic, constituting a dynamic and self-organizing relational structure capable of producing a potentially infinite variety of contextual applications. The two levels are united by a stochastic or somatic selection process called contextualization, where feedback from experience assures the evolution of the system. The relational structure itself is composed of archetypes of space and time consciousness that derive from the evolution of the linguistic sign from the signaling behavior of antecedent species. Detailed analyses are provided to explain how the archetypes structure meaning in both the grammatical and lexical spheres, as well as in syntax"--